INVESTMENT AND GEN Z: A PHENOMENOLOGICAL APPROACH - Eliza Noviriani; Lailatul Mukaromah; Ee Zurmansyah (JAT : Journal Of Accounting and Tax, 2026)
Investment trends among Generation Z are often studied solely through a quantitative economic lens, often neglecting the psychological aspects and subjective meanings of their lives as students. This study aims to explore and analyze the lived experiences of Generation Z students in investing. This study uses a qualitative approach with a phenomenological approach. Data were collected through in-depth interviews with five Generation Z students who are planning and actively investing. The phenomenological analysis reveals that investment is rooted in formal and informal knowledge. Gen Z investment behavior is perceived as providing peace of mind, despite their conscious involvement in high-risk speculative instruments such as bitcoin, cryptocurrency, gold, and mutual funds. Subjective norms are reinforced by the social environment. Meanwhile, perceptions of behavioral control are skewed between the convenience of digital technology and constraints such as limited capital, lack of knowledge, and anxiety about financial loss. However, although Generation Z has shown great interest in social and environmental issues, the study results show that their understanding of Environmental, Social, and Governance (ESG) is still relatively minimal and limited.